Comparison of Uphill and Downhill Training Against 100 Meter Sprint Travel Time - Afni, Arunnita Adzemi Nur; Wahyudi, Heri; Hambali, Sumbara (STKIP Paasundan Press, 2023)
Short distance running or sprinting is one of the race numbers in athletics. The achievements of sprint runners can be seen from the results of the time they achieve when running on the track. This study aims to determine the effect of uphill and downhill training on the travel time of the 100 meter sprint in the MAN 7 Jombang athletic extracurricular. In addition, to find out the difference in the effect of uphill and downhill training on the travel time of the 100-meter sprint in extracurricular athletics MAN 7 Jombang. The method used in this study is a quasi-experiment with the Two group Pretest and Posttest Design research design. A total of 20 subjects were taken as participants and divided into two exercise groups, each consisting of 10 people. The instrument in this study used a 100 meter sprint test. Then the data that has been obtained will be tested using the Paired Sample Test t test to determine the effect of treatment, Independent sample test t test to analyze the average difference between the two groups. The results showed that (1) There was a significant influence on uphill training and downhill training on the 100-meter sprint travel time in MAN 7 Jombang athletic extracurriculars. (2) There was no significant difference between the uphill and downhill training groups on the 100-meter sprint travel time in the MAN 7 Jombang athletic extracurricular.